Perbandingan Efektivitas Irigasi Tetes Dan Irigasi Permukaan Terhadap Kelembaban Tanah Dan Efisiensi Air Di Kepulauan Nias - Lilis Sartika Gulo (CV. SINAR HOWUHOWU, 2026)
This study aims to compare the effectiveness of drip irrigation and surface irrigation systems on soil moisture and water use efficiency in the Nias Islands, which are characterized by hilly topography and high but uneven rainfall distribution. The research employs a qualitative approach using a literature study method, reviewing various scientific journals and relevant literature sources. The results indicate that drip irrigation has higher water efficiency (80–95%) and is more capable of maintaining optimal soil moisture stability compared to surface irrigation, which tends to be less efficient and uneven in moisture distribution. Under the geographical conditions of the Nias Islands, drip irrigation is more suitable as it reduces water loss and minimizes the risk of soil erosion. Therefore, drip irrigation is recommended as a more effective and efficient method to enhance agricultural productivity in the region.